‘Digging Deep’ Inside Post-Migration Social Care and Caring: A Critical Realist Relational Sociological Analysis of Service Providers’ and Service Users’ Experiences in the Settlement and Integration Sector in Ontario/Canada - Baczkowska, Magdalena (Université d'Ottawa / University of Ottawa, 2021)
This doctoral research project explores the complexities implicated in ‘modernized’ publicly-funded and regulated settlement and integration services offered at an organization located in Ontario/Canada. Specifically, it delves into the structural, cultural, agential and reflexive dynamics emerging at this particular site and manifestation of post-migration social care. It also focalizes on the nature and purpose of social relations arising from this social service architecture. It especially considers the experiences of people whose lives were contoured by refugeehood, youthhood and service userhood/clienthood. This research effort draws on participations, observations, interviews and documents from an organizational ethnography conducted in 2015, or under the Conservative Government of Stephen Harper. It uses a critical realist relational sociological framework to make sense of research data. Overall, it contributes to forced migration and post-migration social care/ work scholarship through the use of an innovative meta/theoretical lens that detains multiple and diverse intricacies that are often left out by researchers working on the newcomer-serving sector. As the title indicates, this contribution is driven by the metaphor of ‘digging deep’ that probes the ontological social realities beyond those of the directly visible/observable.
Keywords: Canadian settlement and integration sector; Post-migration social care/work; Refugeehood and youthhood; Critical realism; Relational sociology; Organizational ethnography